Principal Leadership in the Implementation of School-Based Management - Rica Widiastuty; Neliwati Neliwati; Muhammad Rifa'i (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to describe the implementation of School-Based Management at SMA Negeri 2 Medan and to describe the strategy and leadership style of the principal in implementing School-Based Management at SMA Negeri 2 Medan. This study uses a qualitative research type with a descriptive approach, the data sources in this study were school principals, teachers, TU staff, students, and committees, and a total of 14 informants. The data collection process is carried out employing observation, in-depth interviews, and document studies, the researcher uses the analysis technique of Miles and Huberman in Sugiono's book in the form of data reduction, data presentation, and verification (concluding) after which an examination of the validity of the data is carried out with credibility, transferability, dependence. and certainty. The results of this study indicate that: (1) Implementation of School-Based Management at SMA Negeri 2 Medan has been well implemented and developed by the school with great programs so this school has become one of the favorite schools in the city of Medan. (2) The strategy carried out by the principal in implementing SBM is by delegating authority, making decisions by deliberation, and in determining policy the principal always holds open meetings, builds communication, and conducts evaluations. (3) The leadership style of the principal of SMA Negeri 2 Medan has a democratic leadership style that always invites his subordinates to work together to achieve the school's vision, mission and goals.